Aqueous Processing of L-Glutathione Capped ZnO Quantum dots for Potential Biomedical Applications. Issue 1797 (18th May 2015) - Feliciano-Crespo, Raquel; Rodriguez, José A; Reyes-Blas, Myrna; Zhong, Chuan-Jian; Perales-Perez, Oscar
ABSTRACT: Medical research has demonstrated the importance of the utilization of stable, fluorescent nanoprobes. The present work addresses the applicability of biocompatible and fluorescent ZnO nanoparticles as probes for detection of pathogens with the aim of achieving extremely low detection limits. For this purpose, ZnO surface must be functionalized for its subsequent interaction with bacterial cellular membrane (coupling), which will allow the corresponding detection and quantification. Herein we will discuss the aqueous synthesis of stable, water soluble and biologically compatible ZnO nanoparticles (NPss) capped with L-glutathione (GSH). The understanding of the interactions between GSH molecules and surface atoms in ZnO QDs became critical to foster the applicability of this nanomaterial in the biomedical and bioengineering fields. In this regard, the GSH/ZnO molar ratios, reaction temperature (40°C and 60°C), time and pH (6-9) became crucial factors to attain suitable tuning of the QDs properties. ZnO/GSH synthesized QDs were characterized by Transmission Electron Microscopy, X-Ray Diffraction, FT-IR, UV-Vis and photoluminescence (PL) spectroscopy. The QDs shape was spherical with a particle size between 80-100nm. The synthesis of ZnO/GSH under different experimental conditions and the corresponding coupling with E. Coli species, are presented and discussed.